Artificial Intelligence in Libraries and Users Satisfaction in Higher Institutions in Nigeria - Dr. Okpokwasili Nonyelum P. (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
The study adopted a correlational research design to find out the relationship between Artificial Intelligence in Libraries and Users Satisfaction in Higher Institutions in Nigeria. The study covered six higher institutions with twelve Departments in Nigeria. The population of the study comprises of 300 lecturers and 3, 200 students from twelve Departments of different levels. A random sampling technique was adopted and Krejcie and Morgan method was used to determine the sample size of 346. A selfdesigned instrument was used with a four point scale. Based on the findings of this study, it is concluded that there was high level of roles played by artificial intelligence in the delivering of libraries services and high level of satisfaction by the users of artificial intelligence in the libraries of higher institutions in Nigeria. Among other things, the study recommends that libraries should intensify efforts in adopting artificial intelligence in the delivery of libraries services for libraries users to gain very high level satisfaction.